Review and modification of the omnibus surveys - Loke, l-Lee. (2008)
Omnibus surveys were carried out regularly by the PWD/LTA to gather basic information on the travel behaviour of Singapore population. To date the PWD/LTA has commissioned four omnibus surveys, namely in December 1990, September 1991, and March 1994 and August 1995. The overall objective of this study was to review the transport-related section in the omnibus surveys commissioned by the PWD/LTA in terms of the design of the survey sample and instrument that is available in the study. The review focussed on the 1995 omnibus survey as it provides the most information about the sampling procedure and the sample composition.